Smart cycling futures: Charting a new terrain and moving towards a research agenda. (July 2019) - Nikolaeva, Anna; te Brömmelstroet, Marco; Raven, Rob; Ranson, James
Abstract: The future of cycling is about to change. At least, this is apparent if we are to believe the multitude of innovators, start-ups, incumbent industries, policy actors and consultants proposing to harness the power of digital techniques to improve and transform cycling experiences, infrastructures, and gadgets. This 'smartification of cycling' is a phenomenon that is increasingly attracting attention and a variety of interests, fuelled both by the processes of transitioning to smart mobility and a boom of attention to cycling in cities worldwide. However, proposed cycling futures, both implicit and explicit, receive little critical scrutiny. Here, we fill this gap by mapping smart cycling innovations and their key features. We examine how innovations are believed to change the way cycling is practiced, made sense of and governed. Using a constructivist grounded theory approach, we analyse 86 website texts of smart cycling innovations and systematically outline changes envisioned by innovators. Having identified tensions between and within a range of promised futures, we conclude that smart cycling futures are multiple and contested, just as cycling presents are. Therefore, we propose a number of questions for further research to advance a more nuanced understanding of the range of futures of smart cycling in academic thinking and potentially to support decision-making at different levels of governance. Understanding diverse, contested, embodied and embedded cycling presents is part and parcel of imagining and co-creating (smart) cycling futures. Highlights: Smart innovations change the way cycling is practiced, made sense of and governed. Smart cycling futures are multiple and fraught with tensions. In mature cycling contexts the bicycle is increasingly treated as a car. Innovations reproduce a contested understanding of responsibility for road safety. Smart cycling may support the trend towards neoliberalisation of transport planning.